Efficacy of umbilical cord mesenchymal stem cell transfusion for the treatment of severe AKI: a protocol for a randomised controlled trial. Issue 2 (21st February 2022) - Yang, Yuanjun; Gao, Jianjun; Wang, Siyang; Wang, Wenjuan; Zhu, Fang-Lei; Wang, Xiaolong; Liang, Shuang; Feng, Zhe; Lin, Shupeng; Zhang, Li; Chen, Xiangmei; Cai, Guangyan
Abstract : Introduction: Acute kidney injury (AKI) is a common and severe clinical problem that is associated with high mortality, a long hospital stays and high healthcare resource consumption. Approximately a quarter of AKI survivors will develop chronic kidney disease. Mesenchymal stem cells (MSCs) are multipotent stem cells with antiapoptotic, immunomodulatory, antioxidative and proangiogenic properties. Therefore, MSCs have been considered as a potential new therapy for the treatment of AKI. Several clinical trials have been performed, but the results have been inconsistent. This trial investigated whether MSCs can improve renal recovery and mortality in patients with severe AKI. Methods and analysis: One hundred subjects suffering from severe AKI will participate in this patient-blinded, randomised, placebo-controlled, parallel design clinical trial. Participants will be randomly assigned to receive two doses of MSCs or placebo (saline) on days 0 and 7. Urinary biomarkers of renal injury and repair will be measured using commercially available ELISA kits. The main outcome measures are changes in renal function levels within the first 28 days following MSC infusion. Ethics and dissemination: The study was approved by the Ethics Committee of the Chinese PLA General Hospital. The findings of the study will be disseminated through public and scientific channels. Trial registration number: NCT04194671 .